Extended right hepatectomy with caudate lobe resection using the hilar "en bloc" resection technique with a modified hanging maneuver. Issue 4 (18th January 2016) - Perini, Marcos V.; Coelho, Fabricio F.; Kruger, Jaime A.; Rocha, Flavio G.; Herman, Paulo
Abstract : The hanging liver maneuver is a useful technique to guide the transection of liver parenchyma by lifting a tape passed between the anterior surface of the inferior vena cava and the liver. Modified hanging liver maneuvers have been described in different types of liver resection. Surgical resection of hilar cholangiocarcinoma can involve the portal vein and the caudate lobe for margin clearance. However, hilar dissection and resection of the caudate lobe can be a challenging during the hanging maneuver once the tape is positioned. Herein, we describe a modified hanging liver maneuver for a hilar "en bloc" extended right hepatectomy with portal vein resection for the treatment of hilar cholangiocarcinoma including the caudate lobe. J. Surg. Oncol. 2016;113:427–431 . © 2016 Wiley Periodicals, Inc.